A worldwide survey on perioperative antimicrobial prophylaxis for heart transplantation: From theory to clinical practice. Issue 2 (6th March 2023) - Seminari, Elena; Ladini, Giulia Sofia; Colaneri, Marta; Chow, Jennifer; Bruno, Raffaele
Abstract: Background: The aim of our survey was to analyze the current attitudes toward antimicrobial prophylaxis in heart transplanting centers worldwide. Methods: The survey was composed of a total of 50 questions, it consisted of four different sections as follows. The first section collected physicians' personal data and centers' general characteristics, second assessed the approach to patients colonized with multidrug‐resistant organisms (MDROs), while the third consisted of the infection risk related to cardiovascular devices, and antimicrobial treatment data, the last focused on donor's colonization. Results: A total of 56 answers from 26 different countries were collected, mostly from Europe ( n = 30) and the USA ( n = 16). A first‐generation cephalosporin (58.9%) or a combination therapy with vancomycin (10.7%) were the most frequently prescribed antimicrobial prophylaxis. Roughly 30% of the centers used different antimicrobial prophylaxis, mostly including Gram negative bacteria coverage. The frequency of screening for multidrug resistant Gram‐negative bacteria was higher in Europe, where the percentage of centers providing screening for extended spectrum beta‐lactamase (46.7%) and carbapenem‐resistant Enterobacteriaceae (CRE) (53.3%) was higher than in other geographic area ( p = .019; p = .013, respectively). Conclusion: This survey highlights a heterogeneity of clinical practice concerning antimicrobial prophylaxis at transplant. The concern for potential Gram‐negative bacteria infection was responsible for broader antimicrobial coverage in 30% of centers. Abstract : In the heart transplant setting, the choice of antibiotic prophylaxis widely differs among centers, particularly with new concerns arising, such as infections due to Gram‐negative bacteria. The aim of our survey was to analyze the current attitudes toward antimicrobial prophylaxis for HT in transplant centers worldwide.